Implementasi Kurikulum Merdeka dalam Penguatan Karakter Siswa melalui Mata Pelajaran Budi Pekerti di Era Digital - Amirrudin Zalukhu (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to understand the implementation of the Independent Curriculum in the formation of student character, with a special focus on the role of the Budi Pekerti subject. Using a qualitative approach with a descriptive method, data were collected through direct observation and literature studies, then analyzed inductively. The results of the study indicate that the Independent Curriculum provides flexibility for educational units in adjusting the learning process to local needs and developments. This curriculum emphasizes experience-based learning and character strengthening through various active approaches such as project-based learning and problem-based learning. The digital era brings its own challenges to student character, especially in terms of social interaction and the influence of negative content from the internet. In this context, the Budi Pekerti subject has a central role in instilling moral and ethical values, although its implementation still faces obstacles, such as limited learning time. This study emphasizes the importance of integrating character values ​​in all subjects as well as collaboration between teachers and parents in forming student character based on Pancasila values ​​and ready to face future challenges.  Keywords: Digital Era, Independent Curriculum, Character Education, Moral Education